EFFECT OF EDUCATION AND TRAINING, CAREER DEVELOPMENT AND POSITION PLACEMENT ON PERFORMANCE OF EMPLOYEES ALMUSLIM UNIVERSITY BIREUEN DISTRICT - Mirza, Mirza; Konadi, Win; Mukhlis, Mukhlis (IndOmera, 2020)
The study was conducted at the University of Almuslim Bireuen, with the aim to find out; 1) The Effect of Education and Training on Employee Performance, 2) The Effect of Career Development on Employee Performance, and 3) The Effect of Position Placement on Employee Performance. The research method used is descriptive and verification research. Data analysis with the path analysis model (Path Analysis). Descriptive research is research that aims to obtain a description of the training, career development, job placement and employee performance at Almuslim Bireuen University. While verification research basically wants to test the truth of a hypothesis that is carried out through data collection in the field. The sample studied was all employees of Almuslim University with 158 employees. The results of the analysis showed the influence of education and training factors on employee performance at Almuslim University, which amounted to 21.18%. The results of the data analysis also prove the influence of Career Development factors on the performance of Almuslim University employees, which is equal to 20.99%. And from the results of subsequent analysis, it shows that there is an influence of the Employee Position Placement factor on the Performance of Almuslim University employees, which is 14.27%.